Damai Saujana Homestay Agency / Musa Tompang … [et al.] - Tompang, Musa; Mohamat Isa, Masliana; Ramli, Mohd Hafizan; Ramli, Rohazmi; Ahmad, Azura (2004)
Damai Saujana Homestay Agency is the one of the agency that promotes homestay program. The homestay that promoted by our company has its own concept which will be told In Introduction to Homestay. The concepts of Damai Saujana Homestay are: > Located at one place only > Provided only homestay program In promoting homestay program, Damai Saujana Agency has chosen Damai Saujana Homestay, which is located at Kampung Endah, Kuala Langat as the rural area to hold this program. Kampung Endah has the special features that can attract the visitor to come there. Damai Saujana Homestay goal is to present the natural value of the rural area in Malaysia especially in Selangor exactly.